2017
DOI: 10.1016/j.jconrel.2017.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Folate-mediated chemotherapy and diagnostics: An updated review and outlook

Abstract: Folate receptor (FR) is highly expressed in many types of human cancers, and it has been actively studied for developing targeted chemotherapy and diagnostic agents. Tremendous efforts have been made in developing FR-targeted nanomedicines and nanoprobes and translating them into clinical applications. This article provides a concise review on the latest development of folate-mediated nanomedicines and nanoprobes for chemotherapy and diagnostics with an emphasis on in vivo applications. The cellular uptake mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 90 publications
0
52
0
1
Order By: Relevance
“…17 So FA decorated nanoparticle formulations were developed for targeted cancer therapy. [18][19][20] The present research focuses on the development of folate-decorated, pH-sensitive LPNs. Loading carboplatin (CBP) and paclitaxel (PTX), LPNs were expected to combine the therapeutic effects of CBP and PTX, thus show synergistic ability on cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…17 So FA decorated nanoparticle formulations were developed for targeted cancer therapy. [18][19][20] The present research focuses on the development of folate-decorated, pH-sensitive LPNs. Loading carboplatin (CBP) and paclitaxel (PTX), LPNs were expected to combine the therapeutic effects of CBP and PTX, thus show synergistic ability on cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Folate receptor is a kind of glycoprotein anchored to membrane through phosphatidylinositol glycan. [21][22][23] A study has found that folate receptor presents increased expression and activity in many tumor tissues compared with that in normal tissues, which is strongly correlated with clinical stages of tumor. Normal tissues and cells rarely express folate receptor except the expression of placenta, choroid and the low expression of pulmo, thyroid, kidney.…”
Section: Introductionmentioning
confidence: 99%
“…16 FRs are overexpressed in numerous cancers, such as tumors of the ovary, pediatric ependymal brain, mesothelium, breast, colon, kidney, and lung, as well as head and neck carcinomas, but expression is low or nonexistent in most normal tissues, except the kidneys, lungs, and placenta. [16][17][18] Thus, FRs are considered an efficient target for cancer therapy. FA was selected as the targeting ligand since it is one of the bestcharacterized ligands to be exploited for targeting cancer cells.…”
mentioning
confidence: 99%
“…19 Many drug delivery vehicles, such as liposomes, proteins, polymeric NPs, linear polymers, and dendrimers, have been modified with FA to increase their cellular uptake in FR-overexpressing tumor cells. [16][17][18] Epirubicin (EPI)-loaded FA-conjugated pullulan acetate (FPA/EPI) NPs and FAconjugated chitosan-coated poly(d,l-lactide-co-glycolide) NPs might have potential applications in cervical cancer therapy. [20][21][22] Pullulan is a nonimmunogenic, nontoxic, noncarcinogenic, and nonmutagenic material that can be derivatized by chemical reactions with the hydroxyl groups of pyranose rings; therefore, it can be used for targeting drugs and gene delivery.…”
mentioning
confidence: 99%